2021
DOI: 10.3389/fcell.2021.741162
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Ductal Adenocarcinoma: Preclinical in vitro and ex vivo Models

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most overlooked cancers despite its dismal median survival time of 6 months. The biggest challenges in improving patient survival are late diagnosis due to lack of diagnostic markers, and limited treatment options due to almost complete therapy resistance. The past decades of research identified the dense stroma and the complex interplay/crosstalk between the cancer- and the different stromal cells as the main culprits for the slow progress in improving pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 77 publications
(96 reference statements)
0
16
0
Order By: Relevance
“…56,57 Although recent studies have shown the possibility of modeling the PDAC microenvironment in vitro , 17,20,28,33,34,58–61 the tumor-stroma crosstalk remains extremely challenging to reproduce and monitor in functionally effective models. 62–64…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56,57 Although recent studies have shown the possibility of modeling the PDAC microenvironment in vitro , 17,20,28,33,34,58–61 the tumor-stroma crosstalk remains extremely challenging to reproduce and monitor in functionally effective models. 62–64…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Although recent studies have shown the possibility of modeling the PDAC microenvironment in vitro, 17,20,28,33,34,[58][59][60][61] the tumor-stroma crosstalk remains extremely challenging to reproduce and monitor in functionally effective models. [62][63][64] We report herein the design, development and characterization of a multilayer PDAC-on-chip device to mimic the tumorstroma relationship through the culture of human pancreatic ductal epithelial cells expressing the activated KRAS and human pancreatic stellate cells, on the same miniaturized platform. In particular, the HPDE-KRAS cells and the PSCs were respectively seeded in the top and in the bottom layers, separated by an electrospun PCL/gel membrane.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of the used 3D spheroid model is the monoculture of PADC cells. In future studies this model can be further developed by coculturing cancer-associated fibroblasts and immune cells to improve resembling the characteristic dense stroma of PDACs [ 29 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the understanding of pancreatic cancer raises interests among the scientific community, currently developing efficient PDAC in vitro models in order to detect the disease earlier and design effective therapies thus improving patients' prognosis [23][24][25][26][27][28] . Although recent works have shown the possibility of modeling the PDAC microenvironment in vitro 23,24,26,[29][30][31][32][33][34] , the tumor-stroma interplay remains arduous to be replicate and monitor in functionally effective models [35][36][37][38] . Heterotypic 3D spheroids, patient-derived organoids, cancer-on-a-chip platforms, and 3D biofabricated constructs are the currently available bioengineered 3D models mimicking the pancreatic tumor-stroma interplay 16 .…”
Section: Introductionmentioning
confidence: 99%